Successful pregnancy following medical management of heterotopic pregnancy - R Lavanya; K Deepika; Madhuri Patil (Journal of Human Reproductive Sciences, 2009)
We present a case of sonographic demonstration of quadruplet heterotopic pregnancy consisting of twin intrauterine (IU) pregnancy and a twin adnexal pregnancy after ovulation induction (OI) with clomiphene citrate (CC) and timed intercourse (TI). Both heterotopic pregnancy and spontaneous twinning are frequent after OI, this combination although extremely rare must be kept in mind. The role of early transvaginal sonography and serum beta human chorionic gonadotrophin after missed periods helps in early diagnosis. It gives us an opportunity for medical management, saving the patient the agony of surgery along with loss of pregnancy. The management of heterotopic pregnancy is controversial. This patient did not have a viable IU pregnancy and both the sacs in the adnexa were small. Thus, we treated her successfully by medical management with systemic methotrexate, with regular follow-up. This patient successfully conceived after 6 months with OI and TI, with ovulation occurring from the same side of the previous ectopic. She had a viable IU gestation corresponding to 12 weeks.